States and regions in the European Union : institutional adaptation in Germany and Spain - Börzel, Tanja A., 1970- (Themes in European governance., 2002)
Europeanization has led to a significant change in the pattern of Spanish politics, turning rivalry into cooperation. This book thus presents an important analysis of the impact of Europeanization on domestic politics, and on the relationship between states and regions in particular."--Jacket